2019
DOI: 10.1097/md.0000000000013837
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a noninvasive diagnostic criteria for biliary atresia in infants based on the STROBE compliant

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recent studies have investigated the use of other scoring systems to identify BA in infants with cholestasis (3,11,17,27). Kim et al reported that accurate diagnosis of BA among neonates with cholestasis was achieved using a new scoring system that combined clinical, US, and hepatobiliary scintigraphy findings (17).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the use of other scoring systems to identify BA in infants with cholestasis (3,11,17,27). Kim et al reported that accurate diagnosis of BA among neonates with cholestasis was achieved using a new scoring system that combined clinical, US, and hepatobiliary scintigraphy findings (17).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a large ret-rospective cohort, GGT values higher than 500 IU/L were found only in BA patients [64] . Conversely, a normal GGT level is may suggest a poor prognosis [65] as in progressive intrahepatic familial cholestasis type 1 and 2 and other inborn defects of canalicular transport or synthesis of bile acids [63] . Elevated (above 7 μmol/L) total serum bile acids can be considered a very sensitive biomarker of cholestasis.…”
Section: Further Investigationsmentioning
confidence: 99%